Processing of novel nickel free stainless steel by laser powder bed fusion additive manufacturing - Kantonen, Tuomas (My University, 2023)
Additive manufacturing (AM), also commonly known as 3D-printing is a modern manufacturing technology for building products using computer aided design (CAD) models in a layer-by-layer fashion, thereby allowing complex geometries to be produced which might be difficult or even impossible to manufacture traditionally. One of the most widely used AM techniques, especially to build metal products, is laser powder bed fusion (L-PBF) which uses laser to melt material in powder form to create solid parts in a layer wise fashion. As it is with any manufacturing process, the L-PBF produced part quality is strongly dependent on its numerous processing parameters. Therefore, depending on L-PBF process parameters, the produced parts’ characteristics such as density, surface quality, microstructure, properties, etc. can vary widely. These parameters can be related to laser, scanning strategy, powder, and both build plate and powder bed temperatures. Finding optimal building parameters can be very difficult since there are numerous variables in the L-PBF process. Making the process reliably repeatable is one of the biggest current challenges of L-PBF to reach the potential of being industrially worthy manufacturing method. Stainless steels are widely used material group in everyday utensils and in many industrial sectors. Great part of stainless steels include nickel which can cause health hazards and is an expensive element. Due to health issues related to nickel usage, there have been efforts to reduce its utilization especially in products used for biomedical application. Research on processing nickel free steels by L-PBF is in very initial stage. Nickel free steels have many applications in various industries, especially in health technology sector. Since L-PBF has already been identified as a potential manufacturing method to support various health technology business sectors such as biomedical implants, it is worth looking at how L-PBF can be used to process medically relevant Nickel free stainless steels. Therefore, in this study, novel stainless-steel powder with negligible Nickel content (hence Nickel free) was processed using Aconity3d MIDI+ L-PBF machine. Several different L-PBF process parameter combinations were studied to get different volume energy density (VED) to find out optimal combinations to produce dense and deformation free specimens. The study identified laser power, scanning speed and hatching distance as the key process parameters and were optimized. Moreover, the study also investigated the effect of the support structures on specimen deformation and density. Small cuboid shaped specimens were successfully produced with multiple parameter combinations. Defects were seen in lower VED and higher VED specimens. In lower VED specimens delamination and cracking were commonly observed and in higher VED specimens over melting was significant. Four different parameter combinations yielding defect free specimens were chosen for further examinations. Although not in the scope of this study, there were specimens printed for mechanical testing with the chosen combinations for further investigation. The microstructure and phase composition of these specimens was examined in this work. In as-built condition, the austenitic phase was present in small amount, however it was significantly increased through appropriate post-process heat treatments.
Keywords: Additive manufacturing, laser powder bed fusion, nickel free steels, 3D-printing